Pengaruh Iklim Organisasi dan Stres Kerja Terhadap Kepuasan Kerja Perawat: Studi Pada Rumah Sakit Umum Daerah Kabupaten Kolaka Timur - Niar Astaginy; Ismanto Ismanto; Resky Resky (Institut Nalanda, 2023)
This study aims to determine: (1) The Effect of Organizational Climate on Nurse Job Satisfaction (Study at North Koltim Regional General Hospital). (2) Effect of Job Stress on Nurse Job Satisfaction (Study at North Koltim Regional General Hospital). This study uses a quantitative method approach. Collecting data in this study using observation, documentation and questionnaires. The population of this study were all nurses at East Kolaka Hospital. Meanwhile, the sample of this research is 80 nurses with a sample fee using a census technique. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) by testing the measurement model (outer model) and testing the structural model (inner model) with Smart PLS 4. 0. Based on the research results it is known that the Organizational Climate variable has a positive and significant effect on nurse Job Satisfaction as indicated by the P-Values ​​of 0.000. As well as the variable Job Stress also has a negative and significant effect on Nurse Job Satisfaction, this is indicated by the P-Values ​​of 0.004.